Aksjologiczny zamęt wyzwaniem dla współczesnego człowieka - Kmiecikowski , Waldemar (Kultura-Społeczeństwo-Edukacja, 2018)
The article presents the category of axiological confusion understood as an important trait of reality that can be experimentally experienced by a modern man. The man is losing the ability not only to appropriately grasp one’s own human nature and the essence of the moral good, but also the ability of cognitive opening oneself to the intelligibility of being. A modern homo sapiens neutralises the need to seek the truth. After all, the truth ceases to be both a transcendental property of being and a superior value that is the very foundation of a rational discourse on the philosophical imponderabilia.